Trade, technologies, and the evolution of corporate governance - Jan Simon Schymik (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2015)
Do international trade and technological change influence how firms create incentives for human capital? I present a model that incorporates agency problems into a framework with firm heterogeneity and human capital. My model indicates that trade liberalizations and skill-biased technological change alter the way how the largest firms in an economy incentivize their managers. Increases in managerial reservation wages lead to a reduction in corporate governance investments and a rise in performance compensation since monitoring managers becomes less efficient. Using data on CEO compensation and entrenchment opportunities in public industrial firms in the U.S., I document strong empirical regularities in support of the model predictions. Firms allow for more managerial entrenchment and offer larger CEO compensation when their industries become more open to trade or when production becomes more I.T. intensive.
urn:nbn:de:bvb:19-epub-24871-6
Keywords: F1; F16; G34; J33; L22; O33; 330; international trade and firm organization; agency problems in international trade; endogenous managerial entrenchment; corporate governance and CEO compensation